Syphilis and Hepatitis B Co-infection among HIV-Infected, Sex-Trafficked Women and Girls, Nepal - Jay G. Silverman; Michele R. Decker; Jhumka Gupta; Ashwin Dharmadhikari; George R. Seage; Anita Raj (Emerging Infectious Diseases, 2008)
Sex trafficking may play a major role in spread of HIV across South Asia. We investigated co-infection with HIV and other sexually transmitted diseases among 246 sex-trafficked women and girls from Nepal. Those who were HIV positive were more likely than those who were HIV negative to be infected with syphilis and/or hepatitis B.